2015
DOI: 10.2527/jas.2015-9328
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a supplemental candy coproduct as an alternative carbohydrate source to lactose on growth performance of newly weaned pigs in a commercial farm condition

Abstract: The experiment investigated the effects of a supplemental candy coproduct (Chocolate Candy Feed [CCF]; International Ingredient Corp., St. Louis, MO), an alternative carbohydrate source to dietary lactose, on growth performance and on health status of nursery pigs. Crossbred pigs ( = 1,408; 21 d of age and 7.1 ± 0.3 kg BW; Smithfield Premium Genetics, Rose Hill, NC) were randomly assigned to 4 treatments (16 pens/treatment and 22 pigs/pen) in a randomized complete block design: 0, 15, 30, and 45% of lactose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Similarly to our study, in which most of the whey powder was replaced by simple sugars present in FFPs, Guo et al (2015) partially replaced lactose in nursery diets with candy co-products containing about 51% of sugars from the food and candy industries without impairing growth performance, feed intake and feed efficiency. The authors (Guo et al 2015) speculated that partially replacing lactose with carbohydrates from candy co-products could increase feed intake in early nursery phases but may cause a decrease in weight gain in later nursery phases. In fact, as demonstrated by earlier studies, whey powder with sucrose or other sweeteners may increase the feed palatability compared to diets containing only whey powder.…”
Section: Growth Performancementioning
confidence: 53%
See 3 more Smart Citations
“…Similarly to our study, in which most of the whey powder was replaced by simple sugars present in FFPs, Guo et al (2015) partially replaced lactose in nursery diets with candy co-products containing about 51% of sugars from the food and candy industries without impairing growth performance, feed intake and feed efficiency. The authors (Guo et al 2015) speculated that partially replacing lactose with carbohydrates from candy co-products could increase feed intake in early nursery phases but may cause a decrease in weight gain in later nursery phases. In fact, as demonstrated by earlier studies, whey powder with sucrose or other sweeteners may increase the feed palatability compared to diets containing only whey powder.…”
Section: Growth Performancementioning
confidence: 53%
“…It is, thus, widely accepted that piglets benefit from readily digestible carbohydrates until their digestive system is fully capable of utilising raw starch. Previous studies have demonstrated that candy co-products, and the related sugar-rich diet (total sugar content about 20% DM), can be used in a high percentage as an alternative carbohydrate source in diets for nursery pigs up to 12 days post-weaning (Guo et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that these types of alternative feed ingredients need to be investigated in terms of their effects on nutritional and health status. Guo et al (2015) demonstrated that 'candy coproducts can be used to replace up to 45% of dietary lactose for nursery pigs without negative effects on growth performance or health status'. In addition, several studies (Mavromichalis et al 2001;Kim and Allee 2001;Naranjo et al 2010a;Naranjo et al 2010b) have reported that the performance of nursery pigs was not reduced when less than 50% of dietary lactose was replaced by other carbohydrates from cane sucrose (100% sucrose), carbohydrate products (40-75% sucrose), molasses (47% glucose and fructose), or a milk chocolate products (20% lactose and 60% sugar).…”
Section: Discussionmentioning
confidence: 99%